Comparing the safety and efficacy of sodium valproate, levetiracetam, and phenytoin in attenuating the severity of agitation in patients with post-traumatic brain injury: An observational study - Shivani Singh; Raghavendra Nayak; Shivaprakash Gangachannaiah; Ashutosh Bhosale; Reena Sherin Parveen; Varun Kumar S G; Geeta Sundar (PLoS ONE, 2026)
Objective The present study aimed to compare the safety and efficacy of sodium valproate, levetiracetam, and phenytoin in agitation control. Methods and Material This prospective observational study included 189 adult patients with traumatic brain injury (TBI) receiving sodium valproate, phenytoin, and levetiracetam. Agitation was monitored using the Richmond Agitation-Sedation Scale (RASS) at baseline and serially over seven days. The study evaluated the percentage of patients who experienced agitation-relief (A-R) following antiepileptic drugs, along with pattern of adverse events among the three groups. Results Sodium valproate (sod.v) demonstrated better efficacy with 85.7% of patients achieving A-R compared to 63.5% in levetiracetam (P = 0.016). The median time to achieve A-R was 3 days in sod.v and significantly lesser compared to 4 days in phenytoin (P = 0.04) and 5 days in levetiracetam (P = 0.0001). By day 4, 72% of patients in the sod.v achieved A-R, in contrast to 50% in the phenytoin and 31.7% in the levetiracetam group. The safety profile of sod.v and levetiracetam was more favorable with lesser occurrence of adverse events compared to phenytoin (P = 0.017). Conclusions To our knowledge, this is the first pivotal evidence to compare antiepileptics for agitation control in post-traumatic brain injury patients. Our study demonstrated that patients receiving sodium valproate showed relatively greater and earlier improvement in agitation control, with an acceptable safety profile. The study proves the dual benefits of sod.v in post-TBI improving patient outcomes and alleviating mental strain on patients, and their families.